The causes of domestic violence against men - Zahra mirzaei, Mehrangiz Shoaa Kazemi, (Opción, 2019)
This research has been conducted to identify the causes and facts behind domestic violence against men. The research qualitative method was based on Grounded Theory and was implemented in a Semi-Structured interview as the instrument. The results indicated that an inappropriate marriage plays a catastrophic role in this case which brings the other issues as well. This research concludes that the marriage with transient, shallow criteria and unknowns increases the violence possibility and subsequently will lead to an inefficient relationship and multiple frustrations with lack of intimacy, extramarital relations, and sexual disorders.